2018
DOI: 10.3892/ijo.2018.4539
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTTIP promotes renal cell carcinoma progression through the regulation of the miR-615/IGF-2 pathway

Abstract: Emerging evidence has indicated that long non‑coding RNA (lncRNA) HOXA transcript at the distal tip (HOTTIP) regulates cell growth, differentiation, apoptosis and cancer progression. However, the expression and function of HOTTIP in the progression of renal cell carcinoma (RCC) remain largely unknown. In this study, we investigated the role of the lncRNA HOTTIP in RCC. The expression levels of HOTTIP in RCC tissues and cell lines were determined by RT‑qPCR. The association between HOTTIP expression and clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…Results in other cancer types suggest a tumor-suppressive role of let-7i as, for instance, they are downregulated in ovarian and bladder cancer and inhibited tumor proliferation and chemoresistance (Yang et al, 2008;Qin et al, 2019). As for miR-615-3p, Wang Q. et al (2018) found it to be sponged by the lncRNA HOXA transcript at the distal tip (HOTTIP) and to target insulin-like growth factor 2 in RCC. In their study, HOTTIP was shown to be upregulated in RCC tissue, and the overexpression of HOTTIP was reported to promote RCC proliferation, migration, and invasion in vitro, implicating a tumor-suppressive role of miR-615-3p (Wang Q. et al, 2018).…”
Section: Cssmentioning
confidence: 99%
See 1 more Smart Citation
“…Results in other cancer types suggest a tumor-suppressive role of let-7i as, for instance, they are downregulated in ovarian and bladder cancer and inhibited tumor proliferation and chemoresistance (Yang et al, 2008;Qin et al, 2019). As for miR-615-3p, Wang Q. et al (2018) found it to be sponged by the lncRNA HOXA transcript at the distal tip (HOTTIP) and to target insulin-like growth factor 2 in RCC. In their study, HOTTIP was shown to be upregulated in RCC tissue, and the overexpression of HOTTIP was reported to promote RCC proliferation, migration, and invasion in vitro, implicating a tumor-suppressive role of miR-615-3p (Wang Q. et al, 2018).…”
Section: Cssmentioning
confidence: 99%
“…As for miR-615-3p, Wang Q. et al (2018) found it to be sponged by the lncRNA HOXA transcript at the distal tip (HOTTIP) and to target insulin-like growth factor 2 in RCC. In their study, HOTTIP was shown to be upregulated in RCC tissue, and the overexpression of HOTTIP was reported to promote RCC proliferation, migration, and invasion in vitro, implicating a tumor-suppressive role of miR-615-3p (Wang Q. et al, 2018). Chanudet et al (2017) screened for circulating miRNAs in RCC using microRNA arrays in plasma samples of 94 ccRCC patients of all clinical stages and 100 healthy controls.…”
Section: Cssmentioning
confidence: 99%
“…Moreover, overexpression of miR-615 was found to promote cell proliferation and migration and inhibit apoptosis in gastric cancer (10). However, downregulation of miR-615 was found in non-small cell lung cancer and renal cell carcinoma (11,12). In addition, miR-615 was found to play an inhibitory role in esophageal squamous cell carcinoma by targeting IGF2 (13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, MALAT1 directly targeted miR‐429 to improve the proliferation, migration, and invasion abilities of RCC cells . In addition, HOTTIP functioned as a ceRNA for miR‐615‐3p, antagonized its functions in RCC cells . Furthermore, lncRNA HOXA11‐AS positively regulated the expression of miR‐146b‐5p target gene MMP16 to promote the growth and invasion of RCC cells .…”
Section: Discussionmentioning
confidence: 99%